The longer-term effects of human capital enrichment programs on poverty and inequality: Oportunidades in Mexico - McKee, Douglas; Todd, Petra E. (Estudios de Economía, 2016)
Previous empirical research has shown that Mexico's Oportunidades program has succeeded in increasing schooling and improving health of disadvantaged children. This paper studies the program's potential longer-term consequences for the poverty and inequality of these children. It adapts methods developed in DiNardo, Fortin and Lemieux (1996) and incorporates existing experimental estimates of the program's effects on human capital to analyze how Oportunidades will affect future earnings of program participants. We nonparametrically simulate earnings distributions, with and without the program, and predict that Oportunidades will increase future mean earnings but have only modest effects on poverty rates and earnings inequality.